PENERAPAN MODEL PEMBELAJARAN KREATIF-KRITIS DALAM MATA KULIAH SOSIOLOGI PENDIDIKAN - Tutuk Ningsih (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2011)
This study aims to (1) form critical and creative learning models in Sociology of Education learning relevant for students, (2) examine student response to a critical-creative learning in Sociology of Education learning courses, and (3) examine the influence of the creative-critical learning model for improving the quality of learning outcomes in students majoring in Sociology of Education on Tarbiyah Departement at STAIN Purwokerto. This research is a classroom action research. The process of action research carried out using two cycles (cyclic), taking into account the following four main components, namely: planning, implementation, monitoring, and reflection. The first cycle consists of two stages with three acts. The second cycle consists of one stage and one effectiveness measurement to the implementation of creative-critical learning model. The fact analysis was performed along with a qualitative description of the reflection and evaluation of the model. Meanwhile, non-parametric statistical analysis and simple statistics were used to examine the impact of creative-critical learning model for improving the quality of learning. The results provide some conclusions as follows: (1) creative-critical learning model that is suitable for students include procedures and measures as follows, which includes: planning, implementation, monitoring and evaluation of learning, reflection, and assessing of the successful action. This model uses a minimum of two cycles, where the First Cycle consists of 3 actions, and the Second Cycle consists of one stage and one action that is implementing a critical-creative learning models that are effective, (2) The response of students to learning critical creative tend to be more positive than using conventional learning, and (3) students' learning achievement using a learning model of creative-critical indicate a better condition compared with conventional learning. Based on these results IPS-learning facilities are suggested, especially laboratories need to be developed and equipped to facilitate the learning process of applying the various models and strategies in accordance with the characteristics of certain subject areas including sosial studies courses Sociology of Education.